2018
DOI: 10.1515/jomb-2017-0045
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Education and Training Given to Phlebotomists for Reducing Preanalytical Errors

Abstract: SummaryBackgroundThe most common sources of error in the preanalytical phase are considered to be at the stage of patient preparation and sample collection. In order to reduce the preanalytical errors, we aimed to determine the level of phlebotomists knowledge about the preanalytic phase before and after planned trainings in the study.MethodsTraining about preanalytical processes was given to the 454 health professionals and the majority of them were employed as nurse. Questionnaires before and after training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…Indeed, previous studies confirmed an increase in some of the oxidative stress biomarkers, as well as a decrease in the antioxidant defence system in individuals with overweight/obesity (4, 5). However, it is questionable whether all of these biomarkers can predict MetS since discrepancies in the literature exist considering the relationship between oxidative stress biomarkers and MetS and/or its components (6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous studies confirmed an increase in some of the oxidative stress biomarkers, as well as a decrease in the antioxidant defence system in individuals with overweight/obesity (4, 5). However, it is questionable whether all of these biomarkers can predict MetS since discrepancies in the literature exist considering the relationship between oxidative stress biomarkers and MetS and/or its components (6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16).…”
Section: Introductionmentioning
confidence: 99%
“…Contradictive instructions and unsettled recommendations can adversely affect the phlebotomists' attitudes for change. If personnel believe that following guidelines would result in improved patient outcomes and improved working conditions, they probably would be more likely to change behaviours (18).…”
Section: Discussionmentioning
confidence: 99%
“…The differences between the various parameters measured in the paired aliquots were then assessed with Steel-Dwass-Critchlow-Fligner test (20, 21, 22), with evaluation of Hodges-Lehmann location shift for multiple comparisons among different groups, after verification of values distribution with Shapiro-Wilk test. P-values < 0.05 were considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%